(untitled) (Revista de Ciências Agroveterinárias, 2010)
The aim of this paper was to evaluate the capacity of zinc (Zn) removal in zeolitic materials available in the region of Planalto Catarinenese, in Southern Brazil (Zeobasalt), comparing its efficiency with a commercial zeolite from Cuba (Zeopure). The studies Zn removal capacity by the zeolites were separated in three stages, as follows: (i) no change in the ionic force and no change in solution pH; (ii) no change in the ionic force of the solution in two pH values of 4.5 and 5.5; and (iii) Zn removal in the presence of Cd and Cu. There was no statistical difference between the two zeolites for the mean percentage of Zn removal (98%), in pH 8.3. The adsorbed percentage of Zn was not influenced by the pH increase from 4.5 to 5.5. The presence of Cd e Cu did not influence the percentage of Zn removed.